Theoretical basis of optimal therapy for individual patients in chronic myeloid leukemia : A mathematical approach. Issue 3 (2nd April 2020) - Parajdi, Lorand Gabriel; Precup, Radu; Dima, Delia; Moisoiu, Vlad; Tomuleasa, Ciprian
Abstract: Even if the successful pharmacological therapy for chronic myeloid leukemia has reached today a near normal life expectancy in a patient diagnosed with this malignancy, almost one in four patients will change the line of tyrosin-kinase inhibitors during therapy, may it be due to poor response of due to intolerance to therapy. In this paper, starting from a mathematical characterization of the chronic phase in myeloid leukemia, a theoretical investigation of optimal therapy is undertaken as base for further pharmaceutical research and personalized treatment protocols.